Means of discourse manipulations in political party programs in Spain - I. V. Smirnova (Vestnik MGIMO-Universiteta)
Thanks to different mass media sources, members of any society are well aware of political developments and events and politicians. Every person has his or her own formed political beliefs and affirmations, interpreters other people's actions during political developments and evaluates events that take place. Political forces, in turn, see a person (a potential elector) as an object of external information influence. This lets them use political communication when competing for the power. In the modern democratic society this competition is carried out via parliamentarian debates, politicians' speeches, examining political parties' programs, political agitation and voting. General audience-oriented political discourse implements its function of political information influence. As the goal of any political party's program (as an independent form of text in the system of political discourse) is to win the elections and come to power, thus the audience influence function is one of the most fundamental and serve as the basis for the text. The text of a program itself is characterized by its persuasive orientation towards the audience, which reveal itself in such methods as convincing, argumentation, manipulation and evaluation. All the political programs pertain to parties which are at the power or which are in opposition. The main characteristic of oppositional programs is the criticism of the power, vice versa, the dominant party's programs confirm the correctness of their policy. All the political programs are multi-authored. The written form of any political program lets put into practice a detailed text analysis. This article presents the analysis of the texts of two leading Spanish political parties (the Spanish socialist worker's party and the people's party of Spain).